2016
DOI: 10.1007/s00405-016-4193-0
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm on the tracheoesophageal voice prosthesis: considerations for oral decontamination

Abstract: Objectives The tracheoesophageal puncture (TEP) restores verbal communication after total laryngectomy using a one-way valved voice prosthesis (VP). Microbial colonization can shorten VP device life. Our aims were to investigate patterns of prosthetic and oral colonization, and record changes in VP device life after targeted decontamination. Materials and Methods We conducted a retrospective review of TEP clinic patients who underwent microbial analysis of the VP between 01/2003 and 07/2013. Two subgroups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Candida biofilm formation on the prosthetic surface can lead to deterioration of prosthesis, loosening and leakage requiring replacement. Antifungal agents have been advocated to tackle this problem and help prolong the life span of the prostheses [19,20]. However, the long-term use of antimicrobial and antifungal agents can potentially induce the development of resistant strains and hence needs to use with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Candida biofilm formation on the prosthetic surface can lead to deterioration of prosthesis, loosening and leakage requiring replacement. Antifungal agents have been advocated to tackle this problem and help prolong the life span of the prostheses [19,20]. However, the long-term use of antimicrobial and antifungal agents can potentially induce the development of resistant strains and hence needs to use with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is a naturally occurring fungal species commonly isolated from voice prostheses and is considered to be one of the most prevalent causes of prosthesis failure. Today, nystatin is the most frequently administered antifungal treatment for the prevention of valve failure . The assessment of valve life with or without antifungal treatment was not the aim of this study, and patients who indicated the use of antifungal did not routinely report the quantity of medication use prior to or during the duration of the Dual Valve placement.…”
Section: Discussionmentioning
confidence: 99%
“…Today, nystatin is the most frequently administered antifungal treatment for the prevention of valve failure. 2,8 The assessment of valve life with or without antifungal treatment was not the aim of this study, and patients who indicated the use of antifungal did not routinely report the quantity of medication use prior to or during the duration of the Dual Valve placement. The use of antifungal medication could be evaluated in a subsequent study designed to capture that data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations